2003
DOI: 10.1007/978-94-015-1252-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Glacier and Ice Core Evidence of Climate Change on Annual to Millennial Time Scales

Abstract: Abstract. This paper examines the potential of the stable isotopic ratios, 18 0/ 16 0 (8180ice) and 2H/ 1 H (8Dice), preserved in mid to low latitude glaciers as a tool for paleoclimate reconstruction. Ice cores are particularly valuable as they contain additional data, such as dust concentrations, aerosol chemistry, and accumulation rates, that can be combined with the isotopic information to assist with inferences about the regional climate conditions prevailing at the time of deposition. We use a collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
132
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 44 publications
11
132
0
2
Order By: Relevance
“…The inset is a satellite image of Lake Qinghai, where our sediment site is indicated. [Thompson et al, 2003;Yao and Thompson, 1992], (c) alkenone-based temperature record from Lake Qinghai, using the Chu et al…”
Section: Alkenone Distribution In Lake Qinghaimentioning
confidence: 99%
See 2 more Smart Citations
“…The inset is a satellite image of Lake Qinghai, where our sediment site is indicated. [Thompson et al, 2003;Yao and Thompson, 1992], (c) alkenone-based temperature record from Lake Qinghai, using the Chu et al…”
Section: Alkenone Distribution In Lake Qinghaimentioning
confidence: 99%
“…It is one of the places that will exhibit an unambiguous climate response to anticipated greenhouse warming [Hansen et al, 1988]. Ice core records from this region have already witnessed a unanimous warming trend in the 20th century [Thompson et al, 1993[Thompson et al, , 2003. Precipitation in this region is strongly influenced by Asian monsoons that are driven by the thermally induced pressure gradient between ocean and land.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A.D. 1140 to 1250, coeval with the 'Medieval Warm Period', and a cooler period between ca. A.D. 1300 and 1850, correlated with the 'Little Ice Age' in the northern hemisphere (Thompson et al 2003). Palaeolimnological records from Lake Titicaca (Bolivia) show a wet period from ca.…”
Section: Interpretation and Discussionmentioning
confidence: 94%
“…Examples of these are from Lake Ayauch in the southeastern part of Ecuadorian Amazonia (Bush and Colinvaux 1988), from Rio Napo (Yasuni National Park) in the northwestern Amazon basin of Ecuador (Colinvaux et al 1988a;Weng et al 2002), from Lake Yambo at the Inter-Andean plateau of Ecuador (Colinvaux et al 1988b), from Lake Surucucho in the central Ecuadorian Andes (Colinvaux 1997), from the Colombian Cauca Valley (Berrio et al 2002), from Laguna de Chochos in the eastern Peruvian Andes (Bush et al 2005), from the Junin area in the central Peruvian Andes (Hansen et al 1984(Hansen et al , 1994, from Quelccaya ice-core in the central Peruvian Andes (Thompson et al 1984(Thompson et al , 1986(Thompson et al , 2003, from Lake Titicaca and the surrounding BolivianPeruvian Altiplano (Binford et al 1997) and from the Cuzco region in Peru (Chepstow-Lusty et al 2003). Locations of greater interest for this study are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%